Determinants of the Financial Contribution to the NHS: The Case of the COVID-19 Emergency in Italy - Castiglioni, Cinzia; Lozza, Edoardo (Frontiers in Psychology, 2020)
The COVID-19 pandemic has quickly become an unprecedented challenge for many countries at a global level, requiring a significant amount of financial resources to support the National Healthcare System (NHS). In Italy, most of these resources came from the general public through tax payments and monetary donations. The present work aims to investigate the antecedents of citizens’ willingness to financially support the NHS in a situation of public emergency such as the one related to the COVID-19 outbreak. It also aims to distinguish between the willingness to support the system through two different forms of financial contribution, tax payment and charitable giving. An empirical study was performed in the midst of the Italian public health emergency, while the country was reaching its contagion peak. Results showed that participants were more willing to give a financial contribution when it was framed as a donation rather than as a one-off tax payment. Moreover, it was found that trust in money management was the most important factor in predicting the intention to make a financial contribution to the NHS, either through a tax payment or through charitable giving. The perceived risks with regard to the pandemic, in contrast, had no impact.